2008
DOI: 10.1126/science.1161403
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock in Arabidopsis Roots Is a Simplified Slave Version of the Clock in Shoots

Abstract: The circadian oscillator in eukaryotes consists of several interlocking feedback loops through which the expression of clock genes is controlled. It is generally assumed that all plant cells contain essentially identical and cell-autonomous multiloop clocks. Here, we show that the circadian clock in the roots of mature Arabidopsis plants differs markedly from that in the shoots and that the root clock is synchronized by a photosynthesis-related signal from the shoot. Two of the feedback loops of the plant circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
281
3
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 236 publications
(322 citation statements)
references
References 28 publications
22
281
3
16
Order By: Relevance
“…(2008), who found that only the morning loop genes were scored as rhythmic in roots of plants under LL. The discrepancy was not caused by the difference in ecotype (Ws in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(2008), who found that only the morning loop genes were scored as rhythmic in roots of plants under LL. The discrepancy was not caused by the difference in ecotype (Ws in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these data confirm and extend the organ specificity of the plant circadian system (James et al ., 2008): the root clock has a longer FRP under LL than the shoot clock irrespective of whether roots are illuminated. In addition, the relative amplitude of clock gene expression is lower in dark‐grown roots compared with shoots or light‐grown roots, and direct exposure to light can increase relative amplitude in roots.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations